2010
DOI: 10.2466/05.23.24.27.pms.111.6.947-962
|View full text |Cite
|
Sign up to set email alerts
|

Tactical Skills and Ball Speed during a Field Simulation of Penalty Kick Strategies in Soccer

Abstract: This study investigates the efficacy of intermediate penalty kickers by comparing the effect of applying an automated WiFi system on the field of play to simulate a strategy that takes account of goalkeeper action (dependent) with another for which goalkeeper strategy is irrelevant (independent). Intermediate penalty kickers (n=12) took a pretreatment test of 32 kicks in a "real-play" situation with intermediate goalkeepers (n=3). Two groups of kickers underwent 11 treatment sessions using different strategies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…Knowledge of such approaches (e.g., opponent A tends to kick to the right irrespective of the goalkeeper's actions, or opponent B prefers to wait for the goalkeeper to move) could increase a goalkeeper's chances of saving kicks. Kuhn (1988) used ball speed (Castillo, Oña, Raya, Bilbao, & Serra, 2010) to demarcate the two strategies. After analyzing penalty kicks from European league club matches, he concluded that the keeper-dependent strategy constitutes about three quarters of penalty kicks.…”
Section: Many Goalkeepers In National and International Competition Kmentioning
confidence: 99%
“…Knowledge of such approaches (e.g., opponent A tends to kick to the right irrespective of the goalkeeper's actions, or opponent B prefers to wait for the goalkeeper to move) could increase a goalkeeper's chances of saving kicks. Kuhn (1988) used ball speed (Castillo, Oña, Raya, Bilbao, & Serra, 2010) to demarcate the two strategies. After analyzing penalty kicks from European league club matches, he concluded that the keeper-dependent strategy constitutes about three quarters of penalty kicks.…”
Section: Many Goalkeepers In National and International Competition Kmentioning
confidence: 99%
“…In this case, the non-professional, intermediately skilled players showed similar kicking accuracy irrespective of whether they self-controlled the approach angle or whether it was pre-scribed or externally controlled. Other experimental studies in penalty kicking have used both self-controlled and externally controlled instructions for choosing the side and/or height for the placement of the ball (Morris and Burwitz, 1989; Furley et al, 2012), often in interaction with other penalty kick strategies (Castillo et al, 2010). Yet, these studies did not systematically manipulate and compare the efficacy of self- and externally controlled kicks.…”
Section: Introductionmentioning
confidence: 99%
“…On its basis an analysis of goalkeepers' game during the World the European Championships in 2008-2012 was carried out [22,23,24,25,26]. In addition, the literature survey shows that the most common direction for research on goalkeepers' actions are analyses of the efficiency of their actions in situations of defending penalty kicks [27,28].…”
Section: Introductionmentioning
confidence: 99%
“…The efficiency of actions of goalkeepers in futsal Balt J Health Phys Act 2015;7(4):[15][16][17][18][19][20][21][22][23][24][25][26][27] …”
mentioning
confidence: 99%